2009
DOI: 10.1248/bpb.32.1947
|View full text |Cite
|
Sign up to set email alerts
|

1,1-Diphenyl-2-picrylhydrazyl Radical Scavenging Activity of Bee Products and Their Constituents Determined by ESR

Abstract: The aim of this work was to investigate the antioxidant property of honeybee products and their constituents using an ESR method. Antioxidative activity was evaluated as the scavenging activity of 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical. The DPPH radical scavenging activities, in descending order, were: ethanol extract of Chinese red propolisϾ Ͼethanol extract of Brazilian green propolisϾ Ͼwater extract of Brazilian green propolisϾ Ͼethanol extract of bee pollen. Many natural compounds are included in Bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
65
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 29 publications
4
65
0
Order By: Relevance
“…As a result, DCQAs, in which two caffeoyl groups combine with quinic acid, showed stronger radical scavenging activity than chlorogenic acid. This fi nding is compatible with Izuta's report (20). They suggested that the effects of DCQAs on the radical scavenging activity may depend on the caffeoyl groups.…”
Section: Discussionsupporting
confidence: 91%
“…As a result, DCQAs, in which two caffeoyl groups combine with quinic acid, showed stronger radical scavenging activity than chlorogenic acid. This fi nding is compatible with Izuta's report (20). They suggested that the effects of DCQAs on the radical scavenging activity may depend on the caffeoyl groups.…”
Section: Discussionsupporting
confidence: 91%
“…The free radicals scavenged by QHYH in these cells were identified as superoxide anions. EPR is the only approach (other than enzymatic detection) that can provide direct evidence of the presence of a free radical [25] . Using spin traps, EPR allows the detection of free radicals with short life spans, such as HO • /O 2 •- [26] .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a report suggests antioxidant properties of propolis using different chemical assays such as scavenging of DPPH radical [4] and superoxide anion [5], may vary due to the differences in the chemical composition of propolis, which depends on its origin of the propolis [6].…”
Section: Introductionmentioning
confidence: 99%